2012
DOI: 10.1007/s00114-012-0917-1
|View full text |Cite
|
Sign up to set email alerts
|

A drowned Mesozoic bird breeding colony from the Late Cretaceous of Transylvania

Abstract: Despite a rapidly improving fossil record, the reproductive biology of Mesozoic birds remains poorly known: only a handful of undisputed, isolated Cretaceous eggs (some containing embryonic remains) are known. We report here the first fossil evidence for a breeding colony of Mesozoic birds, preserved at the Late Cretaceous (Maastrichtian) Oarda de Jos (Od) site in the Sebeş area of Transylvania, Romania. A lens of calcareous mudstone with minimum dimensions of 80 cm length, 50 cm width and 20 cm depth contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
3
37
0
3
Order By: Relevance
“…Such inferences were also used to genetically link enantiornithin skeletal remains and ratite-type eggshells in a coquina-like accumulation from the uppermost Cretaceous of the Tansylvanian Basin that was interpreted as a reworked bird nesting colony by Dyke et al (2012).…”
Section: Conclusion Of the Depositional Circumstances Of The Nestingmentioning
confidence: 99%
“…Such inferences were also used to genetically link enantiornithin skeletal remains and ratite-type eggshells in a coquina-like accumulation from the uppermost Cretaceous of the Tansylvanian Basin that was interpreted as a reworked bird nesting colony by Dyke et al (2012).…”
Section: Conclusion Of the Depositional Circumstances Of The Nestingmentioning
confidence: 99%
“…Oser and Jackson (2014) further supported this hypothesis by Eberth (1990) through observations of abrasion present on these eggshells. On the other hand, fossil eggshells associated with fine sediment (Maxwell and Horner 1994;Kennedy 1997;Dyke et al 2012;Moreno-Azanza et al 2014) (Table 1) may have been transported by nonhydraulic mechanisms, such as mud flow.…”
Section: Size Of Hydraulic-equivalent Clastic Particles For Eggshell mentioning
confidence: 99%
“…Knowing the hydraulic equivalence of particles permits the reevaluation of eggshell assemblages and the size of associated sedimentary particles in previous studies (e.g., Erben et al 1979;Maxwell and Horner 1994;Kennedy 1997;Liang et al 2009;Dyke et al 2012) ( Table 1). Presence of hydraulically equivalent particles in the associated sediment would suggest that a flow transported and then deposited both the eggshells and the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with domestic chicken (Gallus gallus) eggs demonstrated that both hydrated (simulating fresh eggs) and partially dehydrated eggs (simulating incubated eggs) placed on a beach were readily recruited by rising tides; however, only partially dehydrated eggs floated (Hayward et al 1997). These examples provide modern analogs of fossilized eggs that underwent transport prior to preservation (e.g., Dyke et al 2012).…”
Section: Resultsmentioning
confidence: 99%